The Legal Meaning of The Civil Relationship Between an Unmarried Child and His Father and Father's Family in the Perspective of Inheritance Law in Indonesia - Siti Wahyuni Laadiy; Widhiyanti , Hanif Nur; Kusuma Dewi , Amelia Sri (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
AbstrakPenelitian ini membahas makna hukum dari hubungan perdata antara anak luar kawin dengan ayah dan keluarga ayahnya dalam konteks hukum waris di Indonesia. Tujuan utama penelitian adalah untuk mengkaji interpretasi normatif atas frasa “hubungan perdata dengan ayah dan keluarga ayahnya” sebagaimana tercantum dalam Pasal 43 ayat (1) Undang-Undang Perkawinan, setelah Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010, serta menganalisis implikasinya terhadap praktik peradilan, khususnya dalam pemberian hak waris. Metode yang digunakan adalah yuridis normatif dengan pendekatan konseptual dan studi kasus terhadap putusan-putusan pengadilan. Hasil penelitian menunjukkan adanya disparitas putusan hakim yang menggambarkan ketidakkonsistenan dalam penerapan putusan MK, yang berdampak pada ketidakpastian hukum bagi anak luar kawin. Ketidakhadiran norma harmonisasi dan pedoman interpretatif memperparah perbedaan penafsiran antar sistem hukum (perdata, Islam, dan adat). Penelitian ini memberikan kontribusi dengan menawarkan analisis yuridis terhadap frasa kunci tersebut dan menekankan pentingnya perumusan norma implementatif yang terintegrasi untuk menjamin perlindungan hukum dan kesetaraan hak anak tanpa diskriminasi berdasarkan status kelahiran. Kata kunci: Hukum Waris, Hubungan Perdata, Anak Luar Kawin, Pembaruan Hukum, Mahkamah Konstitusi Abstract This study examines the legal meaning of civil relations between out-of-wedlock children and their biological father and the father's family within the context of inheritance law in Indonesia. The main objective is to analyze the normative interpretation of the phrase “civil relationship with the father and his father's family” as stated in Article 43 paragraph (1) of the Marriage Law following Constitutional Court Decision No. 46/PUU-VIII/2010, and to assess its implications in judicial practice, particularly in the granting of inheritance rights. This normative juridical research employs a conceptual and case-based approach by reviewing relevant court decisions. The findings indicate disparities in judicial rulings, revealing inconsistencies in the implementation of the Constitutional Court’s mandate, which contribute to legal uncertainty for out-of-wedlock children. The absence of harmonizing norms and interpretative guidelines exacerbates the divergence in legal interpretations among civil, Islamic, and customary law systems. This research contributes by offering a legal analysis of the key phrase and emphasizes the urgency of formulating integrated implementative norms to ensure legal protection and equal rights for all children, regardless of birth status. Keywords: Inheritance Law, Civil Relations, Unmarried Children, Legal Reform, Constitutional Court